Bartholin gland cyst and abscess: an updated scenario - Das, Shreyasee; Shil, Rahul; N., Dhanpal H. (International Journal of Research in Medical Sciences, 2023)
Bartholin glands are greater vestibular glands and are located on either side of the vaginal opening. They are mainly homologous to the bulbourethral or cowper’s gland in males. These two pea-sized glands secrets mucus which is essential for vaginal lubrication. Bartholin gland cysts are one of the most frequent fluid-filled masses developing in the vulval area. They may develop as cysts first without symptoms, but if left untreated, they can be infectious and can lead to surgical corrections. The incidence rate of Bartholin gland cysts and abscesses is 0.5 per 1000 people per year. In women, it mainly affects aging between 35 and 50 years. The cysts formed due to blockage of the Bartholin gland duct, which further causes retention and cystic dilation. Mainly, the disease happens due to sexually transmitted infections. Needle aspiration, incision, and drainage are the easiest and most reliable treatment options, but they are not carried out due to their high recurrence rate. This Bartholin gland cyst can interfere with the quality of life as the person can suffer discomfort in walking, difficulty in sitting and walking, and discomfort during intercourse. Most of the Bartholin’s gland cysts are also caused by the microorganisms that infect the perineal area. However, Bartholin’s cyst occurs in nulliparous women of childbearing age. Women in the reproductive age group should get counselling regarding the disease to take better precautionary measures to tackle the condition.